Blockchain ​​Technology for Authentication and Validation Social Network Accounts - Althero, Zacky; Syahreza, Jazlan; Ortiz, Alvano (IAIC Bangun Bangsa, 2023)
By distributing personal information and profile pages in blocks and verifying them using blockchain technology, SNS becomes a point of trust. This study proposes a practical and straightforward technical method to authenticate profiles on social networks. Anyone can use this mechanism to authenticate a social media account, increasing the chances of identifying the natural person behind the account. Furthermore, fake accounts are exposed this way, creating a more secure and trustworthy social media environment. Blockchain technology is a participatory mechanism between private information and the blockchain, and only developers are required to modify the properties of the platform directly. The actual personal information of the account holder is stored in encrypted blocks that are difficult to modify, copy or steal and are displayed on the profile page.